(untitled) (Journal of Environmental Microbiology and Toxicology, 2019)
This paper focused on efficiency of selective locally isolated beneficial microorganisms (LIBeM) consortia in bioaugmentation of oil sludge contaminated soil on a laboratory scale. Five different selective microbial consortia LIBeM were obtained from Environmental Microbiology Laboratory, Universiti Malaysia Sabah. The arrangement of aerated static pile (ASP)-bioreactor made up of acrylic materials was developed act as continuous aeration to the soil. Six different sets of treatment containing 10 kg of soil mixed with 20% (v/v) oil sludge with five bacterial strains and natural attenuation consisted of indigenous microbial in the soil as a control plot was utilized. The rates of biodegradation of oil sludge were studied for a period of three months and periodic sampling of soil from each bioreactor was carried out at 7 days of interval. Analysis of Total Petroleum Hydrocarbon (TPH) was done along with physiochemical parameters such as pH, moisture content and microbial population (CFUs) in the soil. The results obtained revealed biodegradation of oil sludge contaminated soil in all set treatments were much higher than Natural attenuation by 12.1 fold. The bioreactor augmented with Consortia 4 proved to be a better performance with 94% of TPH degradation followed by Consortia 2 (91.6%), Consortia 5 (90.1%), Consortia 1 (90%), Consortia 3 (87.5%) and Natural attenuation (27.4%) respectively. The variations of physiochemical parameters that influence the reduction of oil sludge in the soil were also discussed in this paper. High degradation of long chain alkanes was observed between consortia treatment as compared to natural attenuation plots suggested that bioaugmentation using consortia LIBeM decrease the level of oil sludge in contaminated soil. It was noted that, the continuous supplied of oxygen from aerated static pile (ASP)-system into the soil showed a good prospect in bioremediation of oil sludge.